Design And Build Mesh Topology At Muhammadiyah University - M. Arsyil Adhi’im; Arif Senja Fitrani (Universitas Muhammadiyah Sidoarjo, 2021)
With the capacity of the Muhammadiyah University of Sidoarjo campus in 3 places and the use of the internet at the largest University in Sidoarjo and continues to grow every year, it becomes an obstacle if there is an internet blackout on one of the networks in one of the campuses with data on the use of Network Topology. So that buildings at universities that are quite vulnerable can be connected and exchange information locally quickly without worrying about an off condition at one of the internet network sources, wireless hardware has been developed which is a core component of a wireless mesh network that promises high flexibility, reliability, and performance. The concept used in communication is the same between nodes, but there are some differences that are owned by having an academic background and focusing on device users, mobility, and capabilities in the form of implementing wireless technology which is one solution for providing telecommunications infrastructure that can be deployed easily. fast. In this study, the use of the Wireless Mesh Point-To-Point topology system in order to overcome network conditions on one of the networks at the University in particular experienced an off/outage condition.